Improving performance by Na doping of a buffer layer—chemical and electronic structure of the InxSy:Na/CuIn(S, Se)2 thin‐film solar cell interface. (9th February 2018) - Hauschild, Dirk; Meyer, Frank; Benkert, Andreas; Kreikemeyer‐Lorenzo, Dagmar; Dalibor, Thomas; Palm, Jörg; Blum, Monika; Yang, Wanli; Wilks, Regan G.; Bär, Marcus; Reinert, Friedrich; Heske, Clemens; et al.
Abstract: Doping an indium sulfide buffer layer with sodium is a promising route to replace the "state‐of‐the‐art" CdS buffer layer in chalcopyrite‐based thin‐film solar cells, as it achieves efficiencies as high as 17.9% for large‐area devices (30 cm × 30 cm). We report on the chemical and electronic structure of the Inx Sy :Na/CuIn(S, Se)2 (CISSe) interface for thin‐film solar cells by means of photoelectron, soft x‐ray emission, and inverse photoemission spectroscopy. For as‐deposited Inx Sy :Na buffer layers, we find a sulfur‐poor surface and, in comparison to undoped Inx Sy and the standard CdS buffer, derive a large electronic surface band gap of 2.60 ± 0.11 eV. The conduction band offset at the buffer/absorber interface is a spike of 0.32 ± 0.10 eV. After annealing at 200°C to simulate the thermal load of subsequent cell manufacturing processes, an additional diffusion of copper and selenium from the absorber towards the buffer layer surface is observed, leading to a distinct electronic surface band gap decrease of the Inx Sy :Na buffer layer (to 2.11 ± 0.11 eV). We speculate that the diffusion of absorber elements causes a band gap widening at the former absorber surface and that both effects lead to a reduction of the conduction band spike for the buried Inx Sy :Na/CISSe interface after annealing. Abstract : An Inx Sy :Na buffer layer is a promising route to replace the CdS buffer in chalcopyrite‐based thin‐film solar cells, achieving 17.9% efficiency, for large‐area devices. We report on the chemical and electronic structure of the Inx Sy :Na/CuIn(S, Se)2 interface and derive a conduction band offset of 0.32 ± 0.10 eV for the as‐processed interface. After subsequent annealing at 200°C to simulate the thermal load of further process steps, a diffusion of copper and selenium towards the buffer layer surface is observed, reducing the conduction band spike for the buried Inx Sy :Na/CuIn(S, Se)2 interface.